PEEK-based 3D printing material with high interlayer bonding strength and preparation method thereof
Patent Information
- Application Number
- CN202611124526.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-28
- Publication Date
- 2026-10-30
AI Technical Summary
[0003]然而,PEEK用于熔融挤出式3D打印时普遍存在以下问题:首先,打印温度高、设备门槛高
通过流动调节组分的引入,使PEEK熔体在340℃条件下的黏度降低至103Pa·s~104Pa·s范围,实现了喷嘴温度降低30℃~50℃的稳定挤出,有效降低了设备热负荷要求;
Smart Images

Figure REF-OBJ-1785210409378-000001
Abstract
Description
Technical Field
[0001] This invention relates to the field of 3D printing materials, and more particularly to a PEEK-based 3D printing material with strong interlayer bonding strength and its preparation method. Background Technology
[0002] Polyetheretherketone (PEEK) is a high-performance specialty engineering plastic with excellent heat resistance, chemical corrosion resistance, mechanical strength, and dimensional stability, making it valuable in aerospace, medical implants, automotive, and electronics industries. With the development of additive manufacturing technology, PEEK is gradually becoming an important material in the field of high-performance 3D printing due to its high added value and potential for molding complex structural parts.
[0003] However, PEEK commonly presents the following problems when used in fused deposition modeling (FDM) 3D printing: First, it requires high printing temperatures and sophisticated equipment. Traditional PEEK 3D printing typically requires nozzle temperatures exceeding 360°C. To prevent warping, cracking, and interlayer delamination during printing, the printing chamber often needs to maintain a high temperature, significantly increasing equipment costs and energy consumption. Second, it suffers from insufficient melt flow at low temperatures. PEEK itself has a high melting point and rigid molecular chains, resulting in high melt viscosity at lower printing temperatures, which can easily lead to poor extrusion and interlayer wettability. Most importantly, interlayer bonding strength tends to decrease. The weakest mechanical direction in FDM 3D printed parts is usually the Z-axis interlayer direction. If the nozzle temperature is insufficient or cooling is too rapid, the diffusion time of polymer chains between layers is limited, resulting in inadequate interfacial welding and a decrease in interlayer shear strength, tensile strength, and impact resistance.
[0004] Patent CN121652570A discloses a PEEK-based 3D printing material and its preparation method. The material comprises PEEK powder, lignin-grafted glass short fibers, amino-functionalized PEEK, and inorganic fillers. This approach aims to promote fiber dispersion in the matrix and enhance the material's toughness and strength by forming chemical bonds between the amino groups on the side chains of the amino-functionalized PEEK and the hydroxyl groups on the surface of the lignin-grafted fibers. However, this technical solution primarily focuses on improving the interfacial bonding force between the fibers and the resin matrix to achieve toughening. It lacks targeted optimization for the cross-interfacial diffusion process of molecular chains during the fusion welding of layers in the 3D printing process, leaving room for improvement in further enhancing the interlayer bonding strength in the Z-axis direction of the printed part.
[0005] Patent CN110054862A discloses a PEEK composite material suitable for 3D printing, which is composed of nano-hydroxyapatite, nano-Si3N4, polyetheretherketone, polytetrafluoroethylene, carbon fiber, and antioxidants. This approach, through the composite of various inorganic nanoparticles and fibers, enables the manufactured parts to possess high rigidity and good wear resistance. However, due to the introduction of numerous inorganic fillers and polytetrafluoroethylene with low surface energy, these components may exert steric hindrance or shielding effects on the free diffusion of PEEK molecular chains in the molten state. Furthermore, the compatibility differences between different components may lead to an increase in interfacial defect density, affecting the fusion welding quality of the printed parts in the interlayer direction, resulting in a less than ideal improvement in interlayer bonding strength.
[0006] Therefore, there is an urgent need to provide a new PEEK-based 3D printing material system that can still have excellent interlayer fusion and interlayer bonding strength without relying on ultra-high process temperatures. Summary of the Invention
[0007] To address the aforementioned technical problems, this invention provides a PEEK-based 3D printing material with high interlayer bonding strength and its preparation method. By introducing flow-regulating and crystallization-regulating components with specific structures, and in conjunction with the synergistic effect of interface-enhancing components, the rheological behavior and crystallization kinetics of PEEK melt in the temperature range of 320°C to 350°C are altered, increasing the interdiffusion time of molecular chain segments at the interlayer interface after printing and deposition, thereby improving the interlayer welding quality.
[0008] A PEEK-based 3D printing material with strong interlayer bonding, comprising the following components by weight: Polyetheretherketone resin: 80-95 parts; Composite additive: 5 to 20 parts, wherein the composite additive contains both the first additive and the second additive; The first additive is at least one of low-viscosity polyetheretherketone, polyetherketoneketone, and polyethersulfone oligomers; The second additive is at least one of polyetherimide, polysulfone, polyphenylene ether, polyether ketone ketone, organophosphate nucleating agent, surface-modified nanofiller, and maleic anhydride-grafted polyether ether ketone.
[0009] In one embodiment of the present invention, the polyetheretherketone resin is a mixture of 85 parts high-viscosity polyetheretherketone and 10 parts low-viscosity polyetheretherketone; the first additive is the low-viscosity polyetheretherketone; and the second additive is 4 parts polyetherimide and 1 part organophosphate nucleating agent.
[0010] In one embodiment of the present invention, the first additive is polyether ketone ketone; the second additive is a mixture of polyether ketone ketone, surface-modified nanofiller and maleic anhydride-grafted polyether ether ketone; by weight, the polyether ether ketone resin is 88 parts, the polyether ketone ketone is 8 parts, the surface-modified nanofiller is 2 parts, and the maleic anhydride-grafted polyether ether ketone is 2 parts.
[0011] In one embodiment of the present invention, the first additive is a polyethersulfone oligomer; the second additive is polysulfone and polyphenylene ether; by weight, the polyetheretherketone resin is 90 parts, the polyethersulfone oligomer is 3 parts, the polysulfone is 5 parts, and the polyphenylene ether is 2 parts.
[0012] In one embodiment of the present invention, the composite additive is 8 to 15 parts by weight.
[0013] In one embodiment of the present invention, the intrinsic viscosity of the polyetheretherketone resin is 0.85 to 0.95 dL / g; when the first additive contains low-viscosity polyetheretherketone, the melt index of the low-viscosity polyetheretherketone at 380°C and 2.16 kg load is 18 to 25 g / 10 min.
[0014] In one embodiment of the present invention, the surface-modified nanofiller is nano-silica treated with a silane coupling agent, with a particle size of 20-50 nm and a specific surface area of 180 m². 2 / g.
[0015] A method for preparing PEEK-based 3D printing materials, characterized by comprising the following steps: Step 1: Mix the polyetheretherketone resin and composite additives evenly according to the specified weight parts to obtain a mixture; Step 2: Feed the mixture into a twin-screw extruder, melt-extrude at 340-380°C, granulate, and obtain granules; Step 3: The granules are melted and drawn into filaments at 340-360°C using a single-screw extruder, and then cooled and shaped to obtain printing filaments with a diameter of 1.75 mm.
[0016] In one embodiment of the present invention, in step two, the screw speed of the twin-screw extruder is 80-120 rpm and the feed rate is 15-25 kg / h; in step three, cooling is performed using a cooling water tank at 15-25°C.
[0017] As one embodiment of the present invention, the method further includes a 3D printing step: the printing filament is fused deposition printed under the conditions of nozzle temperature of 320-350°C and cavity temperature of 60-160°C, and the difference between nozzle temperature and cavity temperature is not less than 180°C.
[0018] The present invention has the following advantages over the prior art: By introducing flow-regulating components, the viscosity of the PEEK melt at 340°C was reduced to 10. 3 Pa·s ~ 10 4 Within the Pa·s range, stable extrusion with a nozzle temperature reduction of 30℃~50℃ was achieved, effectively reducing the equipment's thermal load requirements; Through the synergistic effect of crystallization-regulated components, the interdiffusion time of interfacial chain segments is extended to 2s to 10s, and the interlayer bonding strength is increased to more than 1.2 times that of the unmodified material. With the addition of interface-enhancing components, the interlayer porosity was reduced to below 5%, and the interface continuity was significantly improved. A dense interlayer structure can still be obtained under relatively low temperature conditions of 80℃~140℃ in the cavity, which broadens the process window and reduces the dependence on high temperature cavity equipment. The Z-axis interlaminar tensile strength of the printed parts reaches 40MPa~60MPa, and the flexural strength reaches 120MPa~150MPa. The overall mechanical properties meet the requirements of high-end application fields such as aerospace and medical implantation. Detailed Implementation
[0019] The technical solution of the present invention will be further described in detail below with reference to specific embodiments.
[0020] The PEEK-based 3D printing composite material of this invention adopts a multi-component synergistic design concept. Through the scientific formulation of flow-regulating components, crystallization-controlling components, and interface-reinforcing components, stable molding and excellent interlayer bonding performance are achieved under relatively low printing temperatures. The specific implementation of this invention is illustrated below through three concrete examples.
[0021] Example 1 This embodiment provides a PEEK-based 3D printing composite material with high interlayer bonding strength. By weight, its raw material composition is: 85 parts of PEEK resin A, 10 parts of PEEK resin B, 4 parts of polyetherimide (PEI), and 1 part of crystallization regulator.
[0022] Among them, PEEK resin A is Victrex 450G type polyetheretherketone resin with an intrinsic viscosity of 0.85-0.95 dL / g and a melt index of 18-25 g / 10min (380℃ / 2.16kg); PEEK resin B is a low-viscosity PEEK modified material with an intrinsic viscosity of 0.70-0.80 dL / g, used as a flow modifier; polyetherimide PEI is Ultem 1010 type with a glass transition temperature of 217℃ and a thermal decomposition temperature of not less than 500℃, and has good thermodynamic compatibility with PEEK; the crystallization regulator is an organophosphate nucleating agent, which has a significant regulatory effect on the crystallization behavior of PEEK.
[0023] The preparation process is as follows: First, accurately weigh each component according to the ratio and add it to a high-speed mixer for premixing. The premixing time is 3-5 minutes, and the speed is 500-800 rpm. Then, add the premixed material to a twin-screw extruder for melt blending. The barrel temperature of the twin-screw extruder is set to 350℃-380℃, the screw speed is 80-120 rpm, and the feed rate is 15-25 kg / h. After cooling in a cooling water tank, the blended material is granulated by a pelletizer to obtain PEEK-based composite material granules. Finally, the granules are drawn into filaments through a single-screw extruder. The extruder temperature is 340℃-360℃, the cooling water tank temperature is 15℃-25℃, and a printing filament with a diameter of 1.75 mm is obtained through a shaping die and a traction device. The diameter fluctuation is controlled within ±0.05 mm.
[0024] Printing was performed using a fused deposition modeling (FDM) 3D printer. The printing parameters were set as follows: nozzle temperature 340℃, heated bed temperature 160℃, cavity temperature 100℃, layer thickness 0.2mm, and printing speed 20–40mm / s. The temperature difference between the nozzle and cavity was 240℃, which met the requirement of Tn - Tc ≥ 180℃, ensuring that the filament maintained sufficient superheat before deposition.
[0025] The printed parts obtained in this embodiment were tested and verified. The performance test results of the printed parts are as follows: the interlayer tensile strength in the Z direction is 52 MPa, which is 1.37 times higher than the interlayer tensile strength of 38 MPa of unmodified PEEK under the same printing conditions; the flexural strength is 138 MPa; the interlayer porosity is 3.2%, which is significantly lower than the target threshold of 5%; the crystallization peak temperature is 295℃, which is 20℃ higher than the crystallization peak temperature of pure PEEK (315℃), and the crystallization rate is 0.55 times that of pure PEEK.
[0026] Example 2 This embodiment provides another PEEK-based 3D printing composite material, which, by weight, consists of: 88 parts PEEK, 8 parts PEKK, 2 parts surface-modified nano-silica, and 2 parts interface promoter.
[0027] Among them, Victrex 450G type PEEK was selected; AKS9850 type PEKK (polyether ketone ketone) was selected, with a melting temperature of 320-340℃. As a flow modifier, its thermal decomposition temperature is not lower than 340℃, and its melt processing window is 300℃-380℃; the surface-modified nano-silica particles have a particle size of 20-50nm and a specific surface area of 180m². 2 / g, surface treatment was performed using silane coupling agent KH-560 to improve its dispersibility and interfacial compatibility in the PEEK matrix; maleic anhydride-grafted PEEK copolymer was selected as the interfacial accelerator, which can effectively reduce interfacial energy and enhance interlayer bonding.
[0028] The preparation process is as follows: PEEK, PEKK and surface-modified nano-silica are added to a twin-screw extruder in a certain proportion. The barrel temperature is set to 345℃~370℃ and the screw speed is 100rpm. After mixing evenly, the mixture is granulated. An interface promoter is added at the end of the twin-screw extruder through a feeding device for online modification. The resulting composite material granules are drawn into filaments by a single-screw extruder to obtain printing filaments with a diameter of 1.75mm.
[0029] The printing parameters were set as follows: nozzle temperature 345℃, heated bed temperature 170℃, chamber temperature 120℃, layer thickness 0.15~0.25mm, and printing speed 25mm / s. The temperature difference between the nozzle and the chamber was 225℃, which met the process requirements.
[0030] The performance test results of the printed parts are as follows: Z-axis interlaminar tensile strength is 48 MPa, an increase of 1.26 times; flexural strength is 142 MPa; impact strength is 8.5 kJ / m. 2 The heat distortion temperature is 156℃ (under a load of 1.8MPa).
[0031] Example 3 This embodiment provides a PEEK-based 3D printing composite material, which, by weight, consists of: 90 parts PEEK, 3 parts high-temperature flow promoting oligomer, 5 parts amorphous high-temperature polymer, and 2 parts crystallization behavior regulator.
[0032] Among them, the high-temperature flow promoting oligomer is a polyethersulfone (PES) type oligomer with a molecular weight of 2000-5000, a thermal decomposition temperature of not less than 320℃, and a melt processing window of 300℃-380℃; the amorphous high-temperature polymer is polysulfone (PSU) with a glass transition temperature of 190℃, which can regulate the overall crystallization behavior of the material after forming a blend system with PEEK; the crystallization behavior regulator is an asymmetric structure polymer—polyphenylene ether (PPO) with a glass transition temperature of 210℃, which can significantly reduce the crystallization rate of PEEK and prolong the interdiffusion time of chain segments.
[0033] The preparation process is as follows: each component is accurately weighed according to the ratio and added to a twin-screw extruder. The barrel temperature is set to 340℃~365℃, the screw speed is 90rpm, and the feed rate is 20kg / h. After the blended material is cooled and pelletized, it is drawn into printing filaments through a single-screw extruder.
[0034] The printing parameters are set as follows: nozzle temperature 335℃, heated bed temperature 150℃, cavity temperature 80℃, and printing speed 15~30mm / s. The temperature difference between the nozzle and the cavity is 255℃, which ensures the superheat requirement of the fuse even under lower cavity temperature conditions.
[0035] The performance test results of the printed parts are as follows: the Z-axis interlayer tensile strength is 56 MPa, with an increase of 1.47 times; the flexural strength is 128 MPa; the interlayer porosity is 4.1%; and the heat distortion temperature is 152℃. Even at a relatively low cavity temperature of only 80℃, a dense interlayer structure can still be obtained, verifying the significant widening effect of the material system of this invention on the process window.
[0036] Comparative Analysis of Examples To more clearly demonstrate the technical effects of different embodiments of the present invention, the main performance indicators of the three embodiments are compared in tabular form:
[0037] As can be seen from the comparative data above, all three embodiments of the present invention achieve a nozzle temperature reduction of 30°C to 50°C compared to traditional PEEK 3D printing (which typically requires temperatures above 360°C), while the interlayer bonding strength is more than 1.2 times that of unmodified PEEK. Embodiment one focuses on balancing overall performance, achieving excellent interlayer bonding through the synergistic effect of PEI and organic nucleating agents; Embodiment two focuses on reducing melt viscosity, achieving optimal flow properties through the combination of PEKK and nanofillers; Embodiment three focuses on regulating crystallization behavior, achieving the longest interdiffusion time of segments through the combination of PPO and amorphous high-temperature polymers.
[0038] Process parameter optimization and verification This invention further validates the systematic optimization of printing process parameters. Studies show that the difference between nozzle temperature Tn and cavity temperature Tc has a decisive impact on interlayer bonding quality. When Tn - Tc ≥ 180℃, the filament maintains sufficient superheat before deposition, ensuring a good fusion-welding interface between the upper and lower layers. Experimental data show that when Tn - Tc = 180℃, the interlayer bonding strength is 1.18 times that of unmodified PEEK; when Tn - Tc = 240℃, the interlayer bonding strength increases to 1.42 times that of unmodified PEEK.
[0039] The effect of layer thickness on the interfacial interdiffusion time (td) can be described by the following relationship: under the same printing temperature conditions, for every 0.1 mm increase in layer thickness, the required interfacial interdiffusion time increases by approximately 1.5–2.0 s. In this invention, through the synergistic effect of crystallization-controlled components, good interlayer bonding can be achieved within a layer thickness range of 0.1 mm to 0.4 mm.
[0040] Air cooling intensity has a significant impact on crystallization behavior and residual stress. Experiments show that when the air cooling intensity is controlled within the range of 0-30%, the crystallinity and interlayer bonding strength of the part are relatively ideal; excessively high air cooling intensity (such as exceeding 50%) will lead to excessively rapid cooling of the molten wire, insufficient interdiffusion time of chain segments, and a decrease in interlayer bonding strength.
[0041] Based on the above embodiments and process verification, the PEEK-based 3D printing composite material provided by the present invention, through the synergistic design of the material system, can achieve stable extrusion molding and excellent interlayer bonding performance under relatively mild process conditions of nozzle temperature 320℃~350℃ and cavity temperature 60℃~160℃, effectively reducing equipment costs and energy consumption, and broadening the application scope of PEEK materials in the field of 3D printing.
[0042] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A PEEK-based 3D printing material with high interlayer bonding strength, characterized in that, By weight, it consists of the following components: Polyetheretherketone resin: 80-95 parts; Composite additive: 5 to 20 parts, wherein the composite additive contains both the first additive and the second additive; The first additive is at least one of low-viscosity polyetheretherketone, polyetherketoneketone, and polyethersulfone oligomers; The second additive is at least one of polyetherimide, polysulfone, polyphenylene ether, polyether ketone ketone, organophosphate nucleating agent, surface-modified nanofiller, and maleic anhydride-grafted polyether ether ketone.
2. The PEEK-based 3D printing material according to claim 1, characterized in that, The polyetheretherketone resin is a mixture of 85 parts high-viscosity polyetheretherketone and 10 parts low-viscosity polyetheretherketone; the first additive is the low-viscosity polyetheretherketone; the second additive is 4 parts polyetherimide and 1 part organophosphate nucleating agent.
3. The PEEK-based 3D printing material according to claim 1, characterized in that, The first additive is polyether ketone ketone; the second additive is a mixture of polyether ketone ketone, surface-modified nanofiller and maleic anhydride-grafted polyether ketone ketone; by weight, the polyether ketone resin is 88 parts, the polyether ketone ketone is 8 parts, the surface-modified nanofiller is 2 parts, and the maleic anhydride-grafted polyether ketone ketone is 2 parts.
4. The PEEK-based 3D printing material according to claim 1, characterized in that, The first additive is a polyethersulfone oligomer; the second additive is polysulfone and polyphenylene ether; by weight, the polyetheretherketone resin is 90 parts, the polyethersulfone oligomer is 3 parts, the polysulfone is 5 parts, and the polyphenylene ether is 2 parts.
5. The PEEK-based 3D printing material according to claim 1, characterized in that, The composite additive is present in parts by weight of 8 to 15.
6. The PEEK-based 3D printing material according to claim 1, characterized in that, The intrinsic viscosity of the polyether ether ketone resin is 0.85 to 0.95 dL / g; when the first additive contains low-viscosity polyether ether ketone, the melt index of the low-viscosity polyether ether ketone at 380°C and 2.16 kg load is 18 to 25 g / 10 min.
7. The PEEK-based 3D printing material according to claim 1, characterized in that, The surface-modified nanofiller is nano-silica treated with a silane coupling agent, with a particle size of 20-50 nm and a specific surface area of 180 m². 2 / g.
8. A method for preparing the PEEK-based 3D printing material according to any one of claims 1-7, characterized in that, Includes the following steps: Step 1: Mix the polyetheretherketone resin and composite additives evenly according to the specified weight parts to obtain a mixture; Step 2: Feed the mixture into a twin-screw extruder, melt-extrude at 340-380°C, granulate, and obtain granules; Step 3: The granules are melted and drawn into filaments at 340-360°C using a single-screw extruder, and then cooled and shaped to obtain printing filaments with a diameter of 1.75 mm.
9. The method according to claim 8, characterized in that, In step two, the screw speed of the twin-screw extruder is 80-120 rpm, and the feed rate is 15-25 kg / h; in step three, cooling is carried out using a cooling water tank at 15-25℃.
10. The method according to claim 8, characterized in that, The method further includes a 3D printing step: the printing filament is melt-deposited and printed under the conditions of nozzle temperature of 320-350°C and cavity temperature of 60-160°C, and the difference between nozzle temperature and cavity temperature is not less than 180°C.
